Understanding Conflict over Regulation of Platform Work: a Critical Literature Review on the Role of Institutions, Networks and Frames in Policy-Making - Martin-Caballero, Angel (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2023)
AbstractThe expansion of platform work has disrupted and reordered employment regulation. The literature has contributed to this subject from different angles, although often in a fragmented way and without clearly explaining why and how regulatory conflict arises over platform work. Using Beckert's (2010) framework for study of how fields change, the author conducted a critical literature review on: 1) the roles of institutions, networks and frames in regulating platform work; 2) the regulatory power these structures provide to actors and organizations; and 3) the possible interrelationships between these structures. The results show the existence of a substantial literature on the scope of institutional regulation and the regulatory power of networks, but much less on the broader role of the state in this field, and the framing processes that guide the actors’ preferences for regulation. Future lines of research are discussed.SummaryIn this article, a critical review of the literature identifies which state and non-state actors and organizations influence and shape regulatory conflict over platform work, and which resources enable them to intervene.These questions are addressed by examining the different forms of embeddedness that interact and shape the regulatory process. Drawing on the framework that Beckert (2010) proposed to explain changes in market fields, this literature review identifies three dimensions of research that emphasize the roles of institutions, social networks and cognitive frames, respectively. It also discusses to what extent the literature on platform work has developed an integrated perspective on regulation and how the field of industrial relations can benefit from the incorporation of different dimensions of research.The literature search was conducted using the main available databases and grouped into the three main dimensions of the framework. Influential policy reports and grey literature in the field of study were also included. In total, 149 documents were reviewed in depth.The literature has primarily focused on discussing the scope and applicability of existing labour regulatory frameworks and the increasingly important role of strategic litigation. There has also been a remarkable research strand on the regulatory power of platform firms and on new forms of governance. There has been much less critical research on the state's role in the expansion of the platform economy and on how different actors legitimize the regulatory process.This paper applies a three-dimensional framework to the literature to facilitate dialogue on three social structures that influence platform work regulation, the aim being to explain the emergence of regulatory conflict in this area. The framework captures both formal and informal forms of regulation, making it useful for the industrial relations literature as well.